FORMATION OF GRAMMATICAL SKILLS OF TURKMEN STUDENTS ON THE MATERIAL OF RUSSIAN ADJECTIVES - Jumaniyazow, Muzaffar (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2019)
The article is devoted to the pressing issue of formation of grammatical skills of foreign students. The author presents the concept of formation of grammatical skills of Turkmen students taking into consideration their mother tongue. The implementation of this concept is shown on the material of Russian adjectives. The article contains an overview of linguistic research on Russian language by Turkmen linguists, including a comparative aspect. The comparative analysis data was taken into account in the development of materials for the experimental training of Turkmen students. The article describes a complex of exercises which are aimed at the formation of grammatical skills of Turkmen students on the material of adjectives based on their mother tongue. Complexes of exercises that develop these skills include language exercises (choice and completion, transformational, etc.), conditional speech exercises, including exercises based on the text (question-answer, descriptive with graphic or visual aid, etc.), proper speech, creative tasks, providing for the creation of their own texts of various types. The article presents the results of an experiment conducted by us among the foreign students of Pskov State University. As a result, the effectiveness of the developed model of the formation of the grammatical skills of Turkmen students was proved on the basis of adjectives.